(untitled) (Conferencea, 2023)
The author of the article studied the current issues of improving financial control carried out in the sharaoit of the new Uzbekistan. The article will consider the future tasks of the implementation of regulatory documents on state financial control adopted in the Republic of Uzbekistan in the following years by organizations receiving funds from the taxable budget.